Thrombocytosis with acquired von Willebrand disease in an adolescent with sickle cell disease. Issue 1 (20th November 2020) - Yee, Marianne E. M.; Batsuli, Glaivy; Chonat, Satheesh; Park, Sunita
Abstract: Thrombocytosis is common in sickle cell disease and may contribute to vaso‐occlusion. Hydroxyurea treats extreme thrombocytosis. Acquired von Willebrand disease should be considered prior to aspirin therapy. Abstract : Thrombocytosis is common in sickle cell disease and may contribute to vaso‐occlusion. Hydroxyurea treats extreme thrombocytosis. Acquired von Willebrand disease should be considered prior to aspirin therapy.